Altered Synapse Stability in the Early Stages of Tauopathy - Jackson, Johanna S.; Witton, Jonathan; Johnson, James D.; Ahmed, Zeshan; Ward, Mark; Randall, Andrew D.; Hutton, Michael L.; Isaac, John T.; O’Neill, Michael J.; Ashby, Michael C. (Cell reports (Cambridge), 2017)
Synapse loss is a key feature of dementia, but it is unclear whether synaptic dysfunction precedes degenerative phases of the disease. Here, we show that even before any decrease in synapse density, there is abnormal turnover of cortical axonal boutons and dendritic spines in a mouse model of tauopathy-associated dementia. Strikingly, tauopathy drives a mismatch in synapse turnover; postsynaptic spines turn over more rapidly, whereas presynaptic boutons are stabilized. This imbalance between pre- and post-synaptic stability coincides with reduced synaptically driven neuronal activity in pre-degenerative stages of the disease. [Display omitted] •Density of cortical axonal boutons and dendritic spines is reduced early in tauopathy•Abnormalities in synaptic stability and size exist before decreases in synapse density•Turnover of dendritic spines is elevated, whereas presynaptic boutons are stabilized•Neuronal activity is reduced at stages associated with mismatched synaptic turnover Using in vivo two-photon imaging in the rTg4510 tauopathy mouse model, Jackson et al. find that synapse stability is altered during the pre-degenerative stages of tauopathy. Mismatched abnormalities in pre- and post-synaptic turnover coincide with disrupted neuronal activity.